Influence of fluorescence on screening decisions for oral mucosal lesions in community dental practices. (10th June 2013) - Laronde, Denise M.; Williams, P. M.; Hislop, T. G.; Poh, Catherine; Ng, Samson; Bajdik, Chris; Zhang, Lewei; MacAulay, Calum; Rosin, Miriam P.
<x xml:space="preserve">Abstract</x> Background Quality of oral screening examinations is dependent upon the experience of the clinician and can vary widely. Deciding when a patient needs to be referred is a critical and difficult decision for general practice clinicians. A device to aid in this decision would be beneficial. The objective of this study was to to examine the utility of direct fluorescence visualization (FV) by dental practitioners as an aid in decision‐making during screening for cancer and other oral lesions. Methods Dentists were trained to use a stepwise protocol for evaluation of the oral mucosa: medical history, head, neck and oral exam, and fluorescent visualization exam. They were asked to use clinical features to categorize lesions as low (LR), intermediate (IR), or high (HR) risk and then to determine FV status of these lesions. Clinicians made the decision of which lesions to reassess in 3 weeks and based on this reassessment, to refer forward. Results Of 2404 patients screened over 11 months, 357 initially had lesions with 325 (15%) identified as LR, 16 (4.5%) IR, and 16 (4.5%) HR. Lesions assessed initially as IR and HR had a 2.7‐fold increased risk of FV loss persisting to the reassessment appointment versus the LR lesions. The most predictive model for lesion persistence included both FV status and lesion risk assessment. Conclusion A protocol for screening (assess risk, reassess, and refer) is recommended for the screening of abnormal intraoral lesions. Integrating FV into a process of assessing and reassessing lesions significantly improved this model.